2020
DOI: 10.1177/1971400919896264
|View full text |Cite
|
Sign up to set email alerts
|

Review of neuroimaging findings in congenital Zika virus syndrome and its relation to the time of infection

Abstract: Background Many original articles and case series have been published emphasizing the neuroimaging findings of congenital Zika virus (ZIKV) infection. The majority of these studies do not follow a neuroradiological methodology to describe malformations and brain abnormalities resulting from ZIKV infection. The cause-and-effect correlation between the gestational period of maternal infection and the severity of encephalic changes at birth has rarely been reported. A systematic literature review was conducted on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
(32 reference statements)
1
15
0
2
Order By: Relevance
“…In a recent systematic review, the prevalence rates of CNS abnormalities were: reduced brain volume (80–81.5%), subcortical calcifications (88.2–93.3%), microcephaly (90–93.3%) and ventriculomegaly (73.3–78.1%). This study also showed that the prevalence of these abnormalities was inversely proportional to the trimester of pregnancy in which the ZIKV infection occurred [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent systematic review, the prevalence rates of CNS abnormalities were: reduced brain volume (80–81.5%), subcortical calcifications (88.2–93.3%), microcephaly (90–93.3%) and ventriculomegaly (73.3–78.1%). This study also showed that the prevalence of these abnormalities was inversely proportional to the trimester of pregnancy in which the ZIKV infection occurred [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the cohorts might have captured more women infected in the first and second trimesters and others with more women infected in the third. Recently, some studies have shown that the prevalence of microcephaly appears to be inversely proportional to the trimester of pregnancy in which the exposure takes place [ 20 , 35 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 42 articles revealed the most common brain abnormalities following ZIKV exposure in utero, including decreased brain volume, increased extra-axial cerebrospinal fluid space, subcortical calcifications, microcephaly, ventriculomegaly, malformation of cortical development, basal ganglia calcifications, and mega cisterna magna [45]. These findings support the concept that ZIKV interferes with normal neuronal migration during development which then impacts the brain development.…”
Section: Zikamentioning
confidence: 53%
“…Despite this, the MRI aspect of brain lesions secondary to mother-to-child CHIKV transmission is different from other congenital infections, such as cytomegalovirus, Zika, rubella and toxoplasmosis, which can cause microcephaly, cerebral calcifications and malformations of cortical development, which are not seen in CHIKV infection. 1315 In addition, it is important to be aware that on long-term follow-up, patients with perinatal CHIKV infection may experience neurocognitive sequelae and an absence of MRI-detected brain lesions.…”
Section: Discussionmentioning
confidence: 99%